Design and implementation of the ELSA-Brasil biobank: a prospective study in a Brazilian population - Pereira, Alexandre C; Bensenor, Isabela M; Fedeli, Ligia M; Castilhos, Cristina; Vidigal, Pedro G; Maniero, Viviane; Leite, Claudia M; Pimentel, Robercia A; Duncan, Bruce B; Mill, Jose Geraldo; Lotufo, Paulo A (Revista de Saúde Pública, 2013)
The Brazilian Longitudinal Study for Adult Health (ELSA-Brasil) is a multicenter prospective cohort of civil servants designed to assess the determinants of chronic diseases, especially cardiovascular diseases and type 2 diabetes. The present article describes the main design and implementation points of the ELSA-Brasil biobank project. Economic, political, logistical and technological aspects of this study are characterized. Additionally, it discusses the final biorepository protocol and the facilities implemented to achieve this objective. The design and implementation process of the ELSA-Brasil biobank took three years to be performed. Both the central and local biobanks were built according to the best biorepository techniques, using different technological solutions for the distinct needs expected in this study.